2019
DOI: 10.1111/all.13967
|View full text |Cite
|
Sign up to set email alerts
|

Impact of high‐altitude therapy on type‐2 immune responses in asthma patients

Abstract: Background: Asthma patients present with distinct immunological profiles, with a predominance of type 2 endotype. The aim of this study was to investigate the impact of high-altitude treatment on the clinical and immunological response in asthma. Methods: Twenty-six hospitalized asthma patients (nine eosinophilic allergic; EA, nine noneosinophilic allergic; NEA and eight noneosinophilic nonallergic; NN) and nine healthy controls in high altitude for 21 days were enrolled in the study. We assessed eosinophils, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 58 publications
(103 reference statements)
8
37
0
Order By: Relevance
“…158Several earlier studies have highlighted the impact of high-altitude treatment in atopic dermatitis and asthma 159,160. A recent study by Boonpiyathad et al161 described the clinical and immunological changes after high-altitude treatment in asthma patient subgroups and showed that clinical improvement is dependent on the asthma phenotype. Furthermore, high-altitude treatment reduced the type 2 immune response and corrected the elevated CRTH2 expression and its dysregulated functions 161.…”
mentioning
confidence: 99%
“…158Several earlier studies have highlighted the impact of high-altitude treatment in atopic dermatitis and asthma 159,160. A recent study by Boonpiyathad et al161 described the clinical and immunological changes after high-altitude treatment in asthma patient subgroups and showed that clinical improvement is dependent on the asthma phenotype. Furthermore, high-altitude treatment reduced the type 2 immune response and corrected the elevated CRTH2 expression and its dysregulated functions 161.…”
mentioning
confidence: 99%
“…There is compelling evidence of a close relationship between rhinitis and asthma. [2][3][4] Epidemiological studies have shown that most of the patients with asthma have concomitant rhinitis, and the presence of rhinitis is an increased risk factor for the development of asthma. [2][3][4] Patients with asthma and rhinitis share common physiopathologic mechanism including heightened airway hyperresponsiveness and heightened reactivity to lots of stimuli.…”
mentioning
confidence: 99%
“…[2][3][4] Epidemiological studies have shown that most of the patients with asthma have concomitant rhinitis, and the presence of rhinitis is an increased risk factor for the development of asthma. [2][3][4] Patients with asthma and rhinitis share common physiopathologic mechanism including heightened airway hyperresponsiveness and heightened reactivity to lots of stimuli. [2][3][4] Therapeutic studies have demonstrated that the treatment of rhinitis can improve asthma and vice versa.…”
mentioning
confidence: 99%
See 2 more Smart Citations